Amazon water lenses and the influence of the North Brazil Current on the continental shelf - Prestes, Yuri O.; Silva, Alex Costa da; Jeandel, Catherine (Continental shelf research, 2018)
The exchange processes on the Amazon continental shelf in northern Brazil are subject to complex interactions that involve forcings derived from distinct sources. The Amazon shelf is a unique and highly dynamic environment in which considerable discharge of freshwater enters the Atlantic Ocean, producing extensive Amazon Water Lenses (AWL). In addition to the presence of the AWL, the shelf is influenced by the semidiurnal oscillations of the tides and the strong North Brazil Current (NBC), a boundary current of the western Atlantic. The present study was based primarily on the influence of the freshwater input and the NBC on the shelf and the Amazon Shelf Break (ASB) off the mouth of the Pará River. For this purpose, hydrographic and hydrodynamic data were obtained by moorings of the AMANDES Project (April–July 2008), located on the Amazon shelf and the ASB. Spectral analysis and the continuous wavelet transform were applied to define tidal (high frequency/short period) and subtidal (low frequency/long period) signals. The results indicated that on both the shelf and the break, the semidiurnal tides are responsible for the residual landward transport and are predominantly across-shelf. Low-frequency motions in the synoptic bands and the AWL are related to spatial changes in the velocity field, mainly on the ASB in the along-shelf direction. The flow of the NBC can be interpreted as an along-shelf low-frequency oscillation capable of altering the spatial configuration of the velocity field, although its influence is perceived only in the absence of the AWL. •These results reflect the dispersion of the estuarine plume from the Amazon and Pará rivers.•The continental shelf and the adjacent slope are controlled by hydrodynamic processes related to mixing and stratification.•The semidiurnal tides are responsible for the residual landward transport and are predominantly across-shelf.•The Amazon Water Lenses are forced mainly by tides, wind stress and the North Brazil Current.